EFFECT OF WORK ATTITUDE, EMPLOYEE COMPETENCY AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: (Study on Employees of PT Bank Tabungan Negara Medan Branch Office Consumer Collection Recovery and Asset Sales Unit Division) - Silviana Marpaung; Onan Marakali Siregar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Employee performance is one aspect that must be considered by the company because if the employee's performance is not appropriate, it will affect the development and progress of the company. Hence, it is crucial to evaluate work attitude and enhance employee skills in their work environment. This study examines how work attitude, employee competency, and the work environment impact employee performance at PT Bank Tabungan Negara Medan Branch Office Consumer Collection Recovery & Asset Sales Unit Division. The data collection method used in this study was primary data obtained by distributing questionnaires while secondary data was obtained through library research. The results unveil that the variable work attitude, employee competency and work environment have a partial and significant effect on employee performance. The variables work attitude, employee competence and work environment also have a simultaneous and significant effect on employee performance. In conclusion, this study emphasizes that work attitude, employee competence, and the work environment are key factors in enhancing employee performance, ultimately benefiting the company's growth and progress, as seen at PT Bank Tabungan Negara Medan Branch Office Consumer Collection Recovery & Asset Sales Unit Division.